A new species of the pagurid hermit crab genus Lophopagurus McLaughlin, 1981 (Crustacea: Decapoda: Anomura) from French Polynesia, and additional record of L. indonesiensis McLaughlin, 1997 from the Philippines - Komai, Tomoyuki; Rahayu, Dwi Listyo (Zootaxa, 2013)
Two species of the pagurid hermit crab genus Lophopagurus McLaughlin, 1981 are reported herein. Lophopagurus (Lophopagurus) minimus n. sp., described on the basis of two females from Tuamotu Archipelago, French Polynesia, appears closest to L. (L.) nanus (Henderson, 1888), but is easily distinguished from the latter by the different shape of the ocular peduncles and the less developed armature of the right cheliped. A single female from the Bohol Sea, the Philippines, is identified with L. (Australeremus) indonesiensis McLaughlin, 1997, a species for which possible synonymy with L. (A.) triserratus has been suggested. The newly collected specimen confirms the validity of the species and represents its second record since the original description.